NUTRIENTS CONCENTRATION ON THE WATER OF TWO URBAN LAGOONS FO FORMIGA CITY - MG - Thebaldi, M. S.; Silva, A. V.; Vilela, N. M. S.; Leal, B. P.; Borges, I. C.; Martins, I. P.; Fernandes, L. R. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Water is the most important natural resource of the Earth, being essential for life, thus, its quality should be preserved. This paper has as objective to analyze the water quality of Fundão and Josino Lagoons, both located in Formiga, at Minas Gerais State. To do this, water samples were collected in different parts of the Lagoons, which have different forms of use and occupation in the surrounding area. From August 2015 to February 2017 were analyzed the following water quality parameters: pH, nitrate, nitrite, ammonia, potassium and phosphorus, all with twenty replications. The results obtained for total phosphorus do not agree with the recommendations presented at Resolution 357/2005 of CONAMA for Class 1 Water Bodies, for both Lagoons, characterizing its waters as eutrophic.